Assessing Muslims’ Willingness To Donate For Cash Waqf Projects: A Contingent Valuation Study In The Southernmost Provinces, Thailand - Hassama, Aris (2024)
Recently, cash waqf has emerged as an innovative financial model, strategically used to secure seed funding for religious, educational, and public facilities in Thailand's southernmost provinces. However, this evolving dimension of donation remains underexplored. This study employs a comprehensive methodology to investigate how socioeconomic and motivational factors influence people's willingness to donate (WTD) to cash waqf projects. The research utilises the Contingent Valuation Method (CVM) and ordinal logistic regression to assess the significant impact of these independent variables on WTD.